A randomised, controlled, two-Centre open-label study in healthy Japanese subjects to evaluate the effect on biomarkers of exposure of switching from a conventional cigarette to a tobacco heating product - Nathan Gale; Mike McEwan; Alison C. Eldridge; Neil Sherwood; Edward Bowen; Simon McDermott; Emma Holmes; Andrew Hedge; Stuart Hossack; Oscar M. Camacho; Graham Errington; John McAughey; et al. (BMC, 2017)
Abstract Background Smoking is a leading cause of numerous human disorders including lung cancer, chronic obstructive pulmonary disease, and atherosclerotic cardiovascular disease. The development of modified risk tobacco products (MRTPs) has been suggested as a possible way to reduce the risks of tobacco smoking by reducing exposure to cigarette smoke toxicants. This study is designed to investigate whether biomarkers of such exposure are reduced when smokers switch from smoking commercial cigarettes to using either a novel or a commercially-available tobacco heating product (THP). Design and Methods This study will assess biomarkers of exposure in current smokers who either remain smoking, switch to THP use, or quit all tobacco use completely, for 5 days. The study is an in-clinic (confinement) two-centre, randomised controlled clinical study with a forced-switching design. Subjects of either gender will be aged 23-55 years (minimum legal smoking age plus 3 years), of Japanese origin and with a verified smoking status (assessed by exhaled breath carbon monoxide and urinary cotinine levels). Subjects will have a usual brand cigarette within the International Organisation for Standardisation (ISO) tar band of 6-8 mg and will be judged to be healthy by medical history, physical examination, vital signs, electrocardiography (ECG), clinical biochemistry and lung function tests. The primary objective of this study is to assess changes within groups in selected biomarkers of exposure (BoE) and of biological effect (BoBE) after a forced switch from a commercial control cigarette to either a menthol or a non-menthol THP. Secondary objectives are to assess between-group differences, to determine nicotine pharmacokinetics for cigarettes and THPs, to assess subject's satisfaction with the study products, and to monitor additional endpoints related to safety and product use. Discussion Data from this study will advance our scientific understanding of the changes in exposure to cigarette smoke toxicants in smokers who switch to using a THP. Trial registrations UMIN000024988 (25th November 2016); ISRCTN14301360 (14th December 2016)